2016
DOI: 10.1186/s12879-016-1841-3
|View full text |Cite
|
Sign up to set email alerts
|

Throat culture positivity rate and antibiotic susceptibility pattern of beta-hemolytic streptococci in children on secondary prophylaxis for rheumatic heart disease

Abstract: BackgroundAmong children diagnosed to have chronic rheumatic valvular heart disease (RHD) in Ethiopia, many have been observed to develop recurrence of rheumatic fever (RF) despite secondary prophylaxis. This study determined the throat culture positivity rate and drug susceptibility pattern of beta hemolytic streptococci (BHS) isolated from children attending a specialized cardiac clinic in Ethiopia.MethodsThroat swabs were collected from 233 children receiving benzathine penicillin injection as secondary pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
11
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 40 publications
8
11
3
2
Order By: Relevance
“…The finding that stopping ARF prophylaxis is independently associated with positive GAS throat culture results is in agreement with previous reports in literature [7,21,23,25]. In the study by…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The finding that stopping ARF prophylaxis is independently associated with positive GAS throat culture results is in agreement with previous reports in literature [7,21,23,25]. In the study by…”
Section: Discussionsupporting
confidence: 93%
“…The 12.9% prevalence of throat GAS colonization found in this study is much higher than that found among 233 children with chronic RHD attending care at a cardiac clinic in Addis Ababa, Ethiopia [7].…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations